Steroids from the Soft Coral Sinularia crassa - Kuei-Ju Chou; Chiung-Yao Huang; Zhi-Hong Wen; Chi-Hsin Hsu; Yang-Chang Wu; Chang-Feng Dai; Jyh-Horng Sheu; Chih-Hua Chao (Marine Drugs, 2012)
One new sterol, crassarosterol A (1), and four new steroidal glycosides, crassarosterosides A–D (2–5) were isolated from the Formosan soft coral Sinularia crassa. The absolute configuration of 1 was determined using the Mosher’s method. The absolute configurations for the sugar moieties of 2–5 were determined by HPLC analysis on the o-tolylthiocarbamates derived from the liberated sugar after acid hydrolysis. Compounds 2 and 4 could significantly inhibit the expression of pro-inflammatory iNOS protein at 10 µM. In contrast, 1–3 were found to stimulate the expression of COX-2 protein at this concentration. Steroids 1 and 4 also showed cytotoxicity toward the selected human liver cancer cells.